COMMUNITY-BASED MARKETING STRATEGIES IN DEVELOPING MARKETS - Moh. Yamin Darsyah; Mercy Reinette Handayani Mantur; Melyana R Pugu; Al-Amin; Eyad Saleh Bani-Domi (Adisam Publisher, 2024)
Community-based marketing strategy is a marketing approach that emphasises building and managing an active community of consumers, users, or fans of a brand, with the aim of creating stronger bonds, increasing loyalty, and driving organic growth through positive social interactions. This approach relies on the creation of shared value between the brand and its members, where two-way communication and active customer participation in various activities are key. This strategy focuses on shared experiences, trust, and values shared within the community to drive engagement, positive word-of-mouth, and ultimately, sustainable market development over time. The research method conducted in this study uses the literature research method. The results show that community- based marketing strategies offer various benefits, including increased customer engagement, positive responses through word-of-mouth, and the ability to obtain real-time feedback that provides opportunities for innovation and fulfilment of customer needs more effectively. However, challenges such as the need for a large investment of resources and the difficulty in measuring short-term ROI mean that this strategy requires a patient and consistent approach. Community-based marketing strategies, with the right approach, can be the key for companies to develop markets in a more sustainable way and increase long-term profits.